Intrapartum pneumomediastinum and subcutaneous emphysema. Issue 1 (21st May 2015) - Denniss, Hermione; Onofrei, Mihaela; McCormick, Alison
Summary: Spontaneous pneumomediastinum associated with subcutaneous emphysema (Hamman's syndrome) is a rare complication of pregnancy, usually occurring in the second stage of labour. We present one case of spontaneous subcutaneous emphysema presenting during the first stage of labour and discuss the pathophysiology, clinical presentation, treatment and prognosis of this condition. This case report highlights the importance of thorough anaesthetic follow‐up of parturients and team work between the midwives and anaesthetists, even though this patient's symptoms and signs were initially incorrectly attributed to the epidural anaesthetic.